Climatenomics Washington, Wall Street, and the economic battle to save our planet - Keefe, Bob, 1966- (Rowman & Littlefield, 2022)
"The battle against climate change is no longer just an environmental or social issue. As shareholders demand corporations protect assets against climate change and the economic impact of environmental disasters suck billions of dollars out of the economy, capitalism itself has become an ally. The economic impact of climate change is rattling the foundation of our economy at its very core. It's blowing up centuries-old industries from automobiles to oil and gas, creating new opportunities for investors and entrepreneurs. It's costing Americans billions of dollars each and every year. And most importantly, it's forcing politicians to pass long-overdue policies that will transform our businesses, our lives and our future like never before. The good news about this economic earthquake is that it just might be the thing that saves our planet. This is the first book to lay out how climate change has become an economic issue above all and how that has changed everything from the business to politics to the outlook for the future. Bob Keefe, executive director of E2, a national, nonpartisan organization dedicated to providing business perspectives on environmental issues, shows readers how this new reality will impact their industries, businesses, jobs, and communities and transform our country's economy. Climatenomics will be essential reading for anyone who cares about business, politics, or the future of our planet"--